Restorative Justice and Recidivism in the Perspective of Islamic Law and Indonesian Positive Law - Syahyudin, Igvan Nagif; Puluhulawa, Moh. Rusdiyanto U.; Mantali, Avelia Rahmah Y. (Yayasan Cahaya Generasi Positif, 2025)
This study interrogates the legal and normative compatibility of applying restorative justice to repeat offenders within Indonesia’s criminal justice framework. Using a normative juridical and qualitative approach, it analyzes statutory provisions, institutional regulations, and a case study of an assault resolved through a restorative mechanism by the Tapa Sector Police in Bone Bolango. The findings reveal a persistent tension between the positivist pursuit of legal certainty and the restorative emphasis on moral rehabilitation and social harmony. Although Police Regulation No. 8 of 2021 explicitly prohibits restorative settlements for recidivists, empirical practice shows that reconciliation can, in certain contexts, produce more equitable and enduring outcomes than punitive sanctions. The study argues that a strict legal exclusion of repeat offenders undermines the humanistic and moral essence of Indonesian law, which aspires to uphold both justice and compassion. It concludes by advocating for the institutionalization of structured discretion, procedural transparency, and inter-agency coordination to harmonize legality with restorative values. Such integration would transform restorative justice from a procedural deviation into a substantive component of Indonesia’s evolving pursuit of humane and balanced justice.